The Interviewer Wore a Flower in Her Hair: The Effect of Hair Ornamentation on Compliance to a Survey Request. Issue 4 (November 2015) - Stefan, Jordy; Jacob, Céline; Guéguen, Nicolas
Studies have shown that restaurant waitresses with hair ornamentation receive higher tips than waitresses without ornaments. However, the effect of such ornamentation on other behaviors has never been explored. In this study, the effect of a female interviewer's hair ornamentation on compliance with a survey request was examined. Male and female passersby walking alone in the street were asked to participate in a short survey on their food consumption by a female interviewer wearing hair ornamentation (a real flower or a barrette with a synthetic red rose decoration) or not. Findings revealed that both types of hair ornamentation were associated with higher compliance with the survey request than in the no-ornamentation condition.